Gamma radiation of the street corners from South zone of Natal city, Rio Grande do Norte, Brazil (Brazilian Journal of Radiation Sciences (BJRS), 2022)
This research had the objective of studying the absorbed dose of the street corner intersections from the South zone of Natal city, Brazil. This city grew up on dune lands, on siliciclastic rocks from Barreiras Formation, these dunes are quartz-sand and have heavy mineral layers bearing uranium and thorium (monazite, xenothymeo, thorianite, ilmenite, rutile, zircon, magnetite and columbite-tantalite). Not all streets in Natal city have paving, in the part with more movement they have asphalt covering over cobblestone, in the less busy have cobblestone covering, and in the quiet streets are in natural dune sand. In situ Gamma radiation measurements were performed with three portable spectrometers model RS-230 with BGO crystal, about 1 meter above the ground. The absorbed dose ranged from 11 to 150 ƞGy/h (MG: 40; Median: 39; SD: 18). In gamma spectrometry measure, Uranium varied between 0.1 to 6.2 Eq.A. ppm (MG: 1.6; Median: 1.4; SD: 1), Thorium between 0.7 to 32 Eq.A. ppm (MG: 6; Median: 5; SD: 3.3), Potassium ranged between 0.1 to 3.9 Eq.A. % (MG: 1.2; Median: 1.2; SD: 0.7). The values ​​of the absorbed dose of external radiation measured in the studied street corners show values lower than the world average of 59 ƞGy/h, and annual effective dose is also lower than the global average value of 0.48 mSv/a. Areas with higher U-K contents correspond to areas with asphalt/cobblestone capping, while areas with higher Th contents correspond to sandy streets and dunes in protected areas. This fact denote a lower radiometric risk to the population.